A cognitive prosthesis for complex decision-making. (January 2017) - Tremblay, Sébastien; Gagnon, Jean-François; Lafond, Daniel; Hodgetts, Helen M.; Doiron, Maxime; Jeuniaux, Patrick P.J.M.H.
Abstract: While simple heuristics can be ecologically rational and effective in naturalistic decision making contexts, complex situations require analytical decision making strategies, hypothesis-testing and learning. Sub-optimal decision strategies – using simplified as opposed to analytic decision rules – have been reported in domains such as healthcare, military operational planning, and government policy making. We investigate the potential of a computational toolkit called "IMAGE" to improve decision-making by developing structural knowledge and increasing understanding of complex situations. IMAGE is tested within the context of a complex military convoy management task through (a) interactive simulations, and (b) visualization and knowledge representation capabilities. We assess the usefulness of two versions of IMAGE (desktop and immersive) compared to a baseline. Results suggest that the prosthesis helped analysts in making better decisions, but failed to increase their structural knowledge about the situation once the cognitive prosthesis is removed. Highlights: A sensemaking support tool is tested using a complex human-in-the-loop experiment. The tool combines what-if simulation, visualization and knowledge representation. A desktop and an immersive version of the tool are compared to a baseline toolkit. Those using the tool make better decisions, yet immersion adds no extra benefit. However, knowledge about relations is not improved by the cognitive prosthesis.